CAPE VERDE: THE NEW WAVE - ORGANIC BANANAS! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Along with seafood, bananas represent one of Cape Verde's few exports. This declining traditional export sector was reactivated by a community-wide desire to find an agricultural means of boosting economic development in the country. For the...